Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

The problem statement, all variables and given/known data:

Suppose a fair coin is tossed $n$ times. Find simple formulae in terms of $n$ and $k$ for

a) $P(k-1 \mbox{ heads} \mid k-1 \mbox{ or } k \mbox{ heads})$

b) $P(k \mbox{ heads} \mid k-1 \mbox{ or } k \mbox{ heads})$

Relevant equations:

$P(k \mbox{ heads in } n \mbox{ fair tosses})=\binom{n}{k}2^{-n}\quad (0\leq k\leq n)$

The attempt at a solution:

I'm stuck on the conditional probability. I've dabbled with it a little bit but I'm confused what $k-1$ intersect $k$ is. This is for review and not homework.

The answer to a) is $k/(n+1)$.

I tried $P(k-1 \mbox{ heads} \mid k \mbox{ heads})=P(k-1 \cap K)/P(K \mbox{ heads})=P(K-1)/P(K).$ I also was thinking about $$P(A\mid A,B)=P(A\cap (A\cup B))/P(A\cup B)=P(A\cup (A\cap B))/P(A\cup B)=P(A)/(P(A)+P(B)-P(AB))$$

share|cite|improve this question
up vote 0 down vote accepted

By the usual formula for conditional probability, an ugly form of the answer is $$\frac{\binom{n}{k-1}(1/2)^n}{\binom{n}{k-1}(1/2)^n+\binom{n}{k}(1/2)^n}.$$ Cancel the $(1/2)^n$. Now the usual formula for $\binom{a}{b}$ plus a bit of algebra will give what you want.

We can simplify the calculation somewhat by using the fact that $\binom{n}{k-1}+\binom{n}{k}=\binom{n+1}{k}$, which has a nice combinatorial proof, and is built into the "Pascal triangle" definition of the binomial coefficients.

As for the algebra, $\binom{n}{k-1}=\frac{n!}{(k-1)!(n-k+1)!}$ and $\binom{n+1}{k}=\frac{(n+1)!}{k!(n-k+1)!}$. When you divide, there is a lot of cancellation.

share|cite|improve this answer
Thank you very much! – bizboy1 Apr 11 '12 at 19:33

Let $X$ be the random variable for the number of heads in $n$ tosses. Then your questions amount to finding the conditional probabilities: $$ \mathbb{P}(X = k-1 | k-1 \leqslant X \leqslant k) = \frac{\mathbb{P}( \{X = k-1\} \cap \{ k-1 \leqslant X \leqslant k \} }{\mathbb{P}( \{ k-1 \leqslant X \leqslant k \}) } = \frac{\mathbb{P}( X = k-1)}{\mathbb{P}( X =k-1) + \mathbb{P}( X =k) } $$ and $$ \mathbb{P}(X = k | k-1 \leqslant X \leqslant k) = \frac{\mathbb{P}( \{X = k\} \cap \{ k-1 \leqslant X \leqslant k \} }{\mathbb{P}( \{ k-1 \leqslant X \leqslant k \}) } = \frac{\mathbb{P}( X = k)}{\mathbb{P}( X =k-1) + \mathbb{P}( X =k) } $$ Both are solved by noting, for $1 \leqslant k \leqslant n$ $$ \frac{\mathbb{P}(X=k-1)}{\mathbb{P}(X=k)} = \frac{\binom{n}{k-1}}{\binom{n}{k}} = \frac{k}{n-k+1} $$

share|cite|improve this answer
Thank you very much! – bizboy1 Apr 11 '12 at 19:34

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.